DETERMINING THE OUTCOME OF REDUCED FUNCTIONING KIDNEY AFTER PERCUTANEOUS NEPHROSTOMY - Agha Mohammad Zubair,; Jamal Mustafa khan,; Najeebullah,; Syed Rafiuddin Shah,; Muhammad Yaqoob Zarkoon,; Rehan Mohsin, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Significant impairment of renal function can result from unilateral urinary tract blockage, especially if the split renal function falls below 20%. Renal function may be preserved with early intervention using percutaneous nephrostomy (PCN). This study uses Technetium-99m Mercaptoacetyltriglycine (MAG-3) scans to assess how well PCN improves renal function in individuals with severe blockage. Methods: Thirty-six individuals with unilateral urinary tract blockage and divided renal function ≤ 20% were enrolled in this prospective investigation. MAG-3 scans were used to evaluate renal function at baseline and after the intervention. Prior to and following PCN, blood urea nitrogen (BUN) and creatinine levels were also measured. To assess changes in renal function and related variables such as age, gender, and comorbidities, paired sample t-tests were used to examine the data. Results: The participants' average age was 41.58 (±14.84) years, and 69.4% of the group were men. The split renal function scores improved significantly after PCN, rising from 16.53 (±1.95) to 23.64 (±3.49) (mean difference: -7.11; 95% CI: -8.54 to -5.68, P<0.001). Creatinine and BUN levels also sharply dropped. The effectiveness of PCN in recovering renal function was confirmed by subgroup analyses that produced similar findings across clinical and demographic parameters. Conclusion: In patients with unilateral blockage and divided renal function < 20%, PCN efficiently improves renal function. In these situations, it is advised as a conventional intervention.